2000
DOI: 10.1177/026119290002800501
|View full text |Cite
|
Sign up to set email alerts
|

The Isolated Perfused Bovine Udder as a Model of Dermal Eicosanoid Release

Abstract: The aim of this study was to examine whether the isolated perfused bovine udder could be used as a suitable in vitro inflammation model. A common in vivo inflammation model is arachidonic acid-induced inflammation in mouse ears. As an in vitro substitute for this model, arachidonic acid was administered topically to the skin of an isolated perfused bovine udder and the subsequent changes in eicosanoid synthesis were examined. As with the mouse-ear model, there was a significant increase in eicosanoid synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Therefore, we have established a com-parable in-vitro model of arachidonic acid-induced skin inflammation. Former studies demonstrated the increase of eicosanoids in arachidonic acid-irritated skin of isolated perfused bovine udders (Ba$ umer & Kietzmann 2000). In this study we have examined the effect of topically and '' systemically '' administered antiphlogistic drugs on the eicosanoid synthesis in the irritated bovine udder skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we have established a com-parable in-vitro model of arachidonic acid-induced skin inflammation. Former studies demonstrated the increase of eicosanoids in arachidonic acid-irritated skin of isolated perfused bovine udders (Ba$ umer & Kietzmann 2000). In this study we have examined the effect of topically and '' systemically '' administered antiphlogistic drugs on the eicosanoid synthesis in the irritated bovine udder skin.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine udders were perfused according to former studies (Kietzmann et al 1993 ;Ba$ umer & Kietzmann 2000). In brief, the organs were collected immediately after the slaughter of healthy cows.…”
Section: Isolated Perfused Bovine Uddermentioning
confidence: 99%
See 1 more Smart Citation
“…for instance, superficial implantation of microdialysis probes in an isolated perfused bovine udder model has been used to study experimental inflammation. Topical application of arachidonic acid led to the release of a number of eicosanoids of which prostaglandin E2 (PgE2) was measured by microdialysis (22). The bovine udder model was also used to study inflammatory reactions to biodegradable titanium implants (23).…”
Section: Experimental Studies In Animalsmentioning
confidence: 99%
“…Moreover, PGE 2 is not species-specific and assay kits for the detection of this eicosanoid are available commercially and have already been used in the bovine system (B€ aumer & Kietzmann, 2000(B€ aumer & Kietzmann, , 2001B€ aumer et al, 2002;Braun & Kietzmann, 2004). Prostaglandin E 2 was also used as read out for the human MAT (Hartung & Wendel, 1995) and in a bovine whole blood assay (Usui et al, 2013).…”
mentioning
confidence: 99%